Reputasi Auditor Memoderasi Cash Holding Terhadap Perataan Laba - Ni Made Sintya Surya Dewi; I Gusti Putu Eka Rustiana Dewi (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
Income smoothing is one of earnings management pattern, managed by fund manager to reduce profit fluctuations to aim profit stable graph during certain period. It purpose to prevent investor misunderstood of a company value. It's necessary for investor to notice each factor that could affect income smoothing to prevent Investor from such an taking self advantage by fund manager. This research has purpose to get empirical evidence about correlation affect of cash holding to moderation income smoothing by auditor reputation. This research was done by bankers company in BEI. Sample of this research was all listed company in BEI started from 2019-2021. Total sample was 27 companies with 81 observation activities. Sample determinations used non-probability methode sampling with purposive sampling. Analytics data used was logistic regression analysis. Based on analysis, the result was cash holding is not affected to income smoothing, in the other than auditor reputation was proved that it couldn't moderate affect cash holding on income smoothing.